PURCHASING DECISION OF RESIDENTIAL PROPERTY IN CITRALAND SURABAYA: EVIDENCE FROM INDONESIA - Sonata Christian; Yusravhika P. Adhianti (International Journal of Accounting, Finance and Business, 2020)
This study aims to determine the effect of advertising, online marketing and event onpurchasing residential property in CitraLand Surabaya, Indonesia. CitraLand Surabaya is anintegrated residential property over 2500 hectares in West Surabaya that is highly sought afterby upper class families in Indonesia. This study is a quantitative research with questionnaireas primary data collection method and using multiple linear regressions for data analysis. Thepopulation in this study were 4.156 families who have purchased residential properties inCitraLand Surabaya. Based on multiple regression analysis shows that purchasing decisionequation are Y = 2,048 +0,187X1 + 0,069X2 + 0,3062X3. The result of this study reveals thatthe effect of advertising, online marketing and event variables only 36,9% toward purchasingresidential property in CitraLand Surabaya. The other findings of this study that onlyadvertising (X1) and Event (X3) have significance individual influence toward purchasingdecision.